Comparison of the Effects of Sensory–Motor Integration and Cognitive Restructuring on Executive Functions and Social Skills in Individuals with Autism Spectrum Disorder - Arjmand , Shahrad; Tehrani, Hassan Mohammad; Manzari Tavakoli , Vahid; Moulayi Zarandi , Hamid (Psychological Research in Individuals with Exceptional Needs, 2026)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder characterized by impairments in social interaction and communication, as well as restricted and repetitive patterns of behavior. Children with this disorder commonly experience substantial difficulties in executive functions and social skills, which may adversely affect their academic and social adjustment. Therefore, identifying and implementing effective interventions to improve these abilities is of particular importance. In recent years, interventions based on sensory–motor integration and cognitive restructuring have received increasing attention as potentially effective approaches for improving cognitive and social functioning in children with autism spectrum disorder. The present study aimed to examine the effectiveness and durability of sensory–motor integration and cognitive restructuring interventions in improving executive functions and social skills among children with autism spectrum disorder. This study employed a quasi-experimental design with pretest, posttest, and two-month follow-up assessments and a control group. The statistical population consisted of students aged 7–12 years with autism spectrum disorder in Kerman, Iran. From this population, 45 participants were selected using purposive sampling and randomly assigned to three groups of 15 participants: the sensory–motor integration group, the cognitive restructuring group, and the control group. The research instruments included the Behavior Rating Inventory of Executive Function (BRIEF) and the Gresham and Elliott Social Skills Rating System (Teacher Form). Data were analyzed using repeated-measures analysis of variance. The results indicated that the effect of time was significant for executive functions (F = 13.90, p < .01) and social skills (F = 9.90, p < .01). In addition, the time × group interaction effect was significant for executive functions (F = 9.90, p < .01, η² = .54) and social skills (F = 9.90, p < .01, η² = .44). Post hoc comparisons showed that both interventions resulted in significant improvements in executive functions and social skills compared with the control group (p < .05). Furthermore, the sensory–motor integration intervention was more effective than cognitive restructuring, and these effects were maintained at the follow-up assessment (executive functions: F = 17.87, p < .01, η² = .45; social skills: F = 12.57, p < .01, η² = .37). Therefore, both interventions are suggested to use to improve executive functions and social skills in individuals with autism spectrum disorder while sensory-motor integration is more effective than cognitive restructuring intervention.